Simulasi Jaringan untuk Sistem Terdistribusi Website “Simple Restaurant App” dengan GNS3 - Rafel Sutra Dharma; Tri Sutisno; Manatap Dolok Lauro; Ari Wijaya; George Wielianto; Michael Michael; Firzi Ilham Bagusti (Lembaga Pengembangan Kinerja Dosen, 2025)
Distributed systems, integral to contemporary computing, involve the coordinated functioning of autonomous nodes across interconnected networks. Architectural models like client-server and peer-to-peer configurations define their structure, presenting both advantages and challenges. Challenges stem from the intricacies of managing geographically dispersed nodes, encompassing issues of data consistency, fault tolerance, scalability, and security. Overcoming these hurdles demands advanced algorithms and protocols, especially for achieving consistency and resilience in the face of failures. Scalability is a critical consideration, and security concerns add complexity to their design. Current trends in distributed systems, such as edge computing, serverless architectures, and blockchain technologies, aim to address these challenges and enhance system capabilities. Edge computing optimizes proximity to data sources, serverless architectures streamline resource utilization, and blockchain offers decentralized and tamper-resistant solutions. Understanding these architectures, addressing challenges, and embracing emerging trends are pivotal for constructing robust and efficient distributed systems that align with the demands of the interconnected digital landscape.